Review of Chemical Characteristics of Antioxidant Compounds and Biological Activities that have the Potential for Pharmaceuticals - Laode Rijai (Journal of Tropical Pharmacy and Chemistry, 2019)
Chemical characteristics of a compound to be an antioxidant compound are more reactive than the compounds making up cells and tissues as well as metabolic component compounds, to radical compounds in the mammalian metabolic system. A highly reactive compound is (1) has one or more unpaired electrons in the form of radical electrons or compounds that lose or excess electrons form ionic (2) have many paired electrons (3) the distance between groups or atoms that have radical electrons very close or distance between same ion in a compound or the distance between groups or atoms which have electron pairs very close in term chemical bond or in space or conformation (4) and compounds that contain a lot of oxygen atoms. Therefore, a group of potential compounds that have strong antioxidant activity is phenolic, especially polyphenols because they have a hydroxy group or another group that has many paired electrons, located in an aromatic ring very close in chemical bonds, or an electron pair between aromatic rings in a very close compound based on space. Furthermore, highly reactive compounds are potentially toxic because they react easily with chemical compounds making up cells and tissues, as well as metabolic component compounds; such as proteins, lipids as fats, carbohydrates, non-fat lipid compounds, and nucleic acids (DNA and RNA). Therefore, the excess of antioxidant compounds in the metabolic system is not good, if there is no free radical in the metabolic system or excessive radical compounds. Thus, the biological activity of antioxidant compounds that must be known if an antioxidant compound will be used in the pharmaceutical field is toxicity. Toxicity information that prospects to be continued as a pharmaceutical antioxidant product is minimally sourced from preclinical testing.